2021
DOI: 10.3390/su132414028
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Selected Beneficial Substances in Peach Fruits

Abstract: Peaches (Prunus persica L.) are a popular and sought-after dessert fruit. This is mainly due to their flavour, aroma, attractive appearance, and high content of substances that play an important role in human nutrition. The present study was carried out to determine some important analytical properties (sugars/sucrose, glucose, fructose and sorbitol), total acid, total phenolics, flavonoids, antioxidant capacity, carotenoids and anthocyanins of 34 selected peach varieties. The analyses are also complemented by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…They are usually consumed fresh, canned or as a component of baked goods. They contain numerous health promoting properties, i.e., cardiovascular health, brain function improvement, non-communicable diseases improvement [ 11 , 12 ]. Due to the above-mentioned properties and their traditional use in culinary technology, peaches can be seen as suitable for being the main ingredient in frozen desserts.…”
Section: Introductionmentioning
confidence: 99%
“…They are usually consumed fresh, canned or as a component of baked goods. They contain numerous health promoting properties, i.e., cardiovascular health, brain function improvement, non-communicable diseases improvement [ 11 , 12 ]. Due to the above-mentioned properties and their traditional use in culinary technology, peaches can be seen as suitable for being the main ingredient in frozen desserts.…”
Section: Introductionmentioning
confidence: 99%
“…During summertime, peaches are one of the most common and commercially‐important fruit tree species of the Mediterranean area. They are also appreciated for their nutritional and sensory properties [7,8] …”
Section: Introductionmentioning
confidence: 99%
“…They are also appreciated for their nutritional and sensory properties. [7,8] There has been an increasing interest in peach nutriment value because of its richness in carotenoids and antioxidant substances, essentially procyanidins, anthocyanins, catechins, and phenolic acids. [9,10] In peaches, phenolic compounds have a crucial role in sensory quality such as visual appearance (pigmentation and browning) and taste (bitter and astringency), [11,12] as well as in nutritional properties due to their potential antioxidant activity which has been proven to provide health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Peaches can serve as a source of sugars, mainly sucrose, as well as phenols, carotenoids and anthocyanins, and also provide valuable antioxidants. In the study from the Czech Republic, the Czech cultivar 'Krasava' was found to have a very high content of titratable acids, phenols, flavonoids and antioxidant capacity [16]. Pomological studies of fruit quality and consumer acceptance can give farmers clues as to which species and cultivars they can grow to be more successful in the market.…”
mentioning
confidence: 99%
“…This time the Special Issue (SI) focused on different fruit species and aspects that can promote more sustainable fruit growing in the future. The SI "Sustainable Fruit Growing: From Orchard to [16] For this valuable collection of data, the editor would like to thank all the authors who submitted their articles for this Special Issue and congratulate them on the publication of their articles with Sustainability. This would not have been possible without the active support of all the Academic Editors and the dedicated reviewers with their constructive comments, for which I am very grateful.…”
mentioning
confidence: 99%